Two new species of Chondrocladia (Demospongiae: Cladorhizidae) with a new spicule type from the deep south Pacific, and a discussion of the genus Meliiderma - Vacelet, Jean; Kelly, Michelle; Schlacher-Hoenlinger, Monika (Zootaxa, 2009)
Two new species of Chondrocladia are described from the deep Pacific, off New Zealand and South Australia. These presumably carnivorous sponges are characterized by the presence of a sheath of special spicules along the stalk, for which the new term ‘trochirhabd’ is coined. Similar spicules were known from fossil strata of the Early Jurassic, suggesting that Cladorhizidae were already present in the Mesozoic. The arrangement of the trochirhabds along the stalk is similar to that described in the genus Meliiderma, which has been synonymized with Chondrocladia. We propose here the revival of Meliiderma as a subgenus of Chondrocladia, for Chondrocladia stipitata Ridley & Dendy, 1887, from the subantarctic Indian Ocean, C. occulta (Lehnert et al., 2006), described from the North Pacific as a species of Latrunculia, and for C. turbiformis sp.nov. and C. tasmaniensis sp.nov. from New Zealand’s Chatham Rise and several Tasmanian seamounts, respectively, described herein.